2022
DOI: 10.3390/ijms231810209
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Promoting Actions of HNRNP A1 in HCC Are Associated with Cell Cycle, Mitochondrial Dynamics, and Necroptosis

Abstract: Hepatocellular carcinoma (HCC) is one of the most frequent malignancies in the world. Although increasing evidence supports the role of heterogeneous ribonucleoprotein particle A1 (HNRNP A1) in tumor progression, the function of HNRNP A1 in HCC remains unclear. Here, we focused on the role of HNRNP A1 in the development of HCC. In this study, we found HNRNP A1 participates in many aspects of HCC, such as progression and prognosis. Our results showed that HNRNP A1 is upregulated in human HCC tissues and cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Dysregulation of hnRNPA1 has been associated with various diseases, including cancer [ 38 ]. For example, hnRNPA1 was overexpressed in lung carcinoma, GC, and colorectal cancer [ 39 ] and has been correlated with poor prognosis in hepatocellular carcinoma and breast cancer [ 40 , 41 ]. In this study, GC patients with high levels of hnRNPA1 had unfavorable overall survival in TCGA database, and upregulation of hnRNPA1 protein expression was observed in OIP5-AS1-overexpressing GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of hnRNPA1 has been associated with various diseases, including cancer [ 38 ]. For example, hnRNPA1 was overexpressed in lung carcinoma, GC, and colorectal cancer [ 39 ] and has been correlated with poor prognosis in hepatocellular carcinoma and breast cancer [ 40 , 41 ]. In this study, GC patients with high levels of hnRNPA1 had unfavorable overall survival in TCGA database, and upregulation of hnRNPA1 protein expression was observed in OIP5-AS1-overexpressing GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal RNA metabolism may have serious consequences for a variety of diseases due to abnormal regulation of RNAbinding proteins (Feng et al, 2022). In fibroblasts (Shimada et al, 2009) and hepatocellular carcinoma (Zhao et al, 2022), downregulation of hnRNP A1 accelerates cellular senescence, and hnRNP A1 expression gradually decreases to undetectable levels during fibroblast senescence (Wang et al, 2016). Aging is the most common risk factor in AD (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that, as the liver progressively ages, necroptosis increases, which in turn continuously exacerbates chronic liver inflammation, thus exacerbating the HCC transition ( 157 ). This necroptosis-mediated liver inflammation process may be prevented by β-carotene and heterogeneous nuclear ribonucleoprotein A1 ( 158 , 159 ). In addition, excess sorbitol dehydrogenase (SORD) in HCC cells could inhibit tumor growth and stemness by enhancing necroptosis signaling, and treatment with human recombinant SORD controlled HCC cell growth and regulated macrophage polarization in the tumor microenvironment ( 160 ).…”
Section: Necroptosis In Hccmentioning
confidence: 99%